2016
DOI: 10.1091/mbc.e16-01-0004
|View full text |Cite
|
Sign up to set email alerts
|

Polo kinase Cdc5 associates with centromeres to facilitate the removal of centromeric cohesin during mitosis

Abstract: Cdc5 associates with centromeric chromatin during mitosis. Cdc5 plays a critical role in the differential removal of cohesin from centromeric chromatin compared to chromosome arms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 97 publications
(109 reference statements)
3
27
0
Order By: Relevance
“…Upon Mcd1p-AID depletion, the binding of Cdc5p was abolished genome-wide (Figure 3 and Figure 3-figure supplement 1, Figure 3-figure supplement 2, Figure 3-figure supplement 3), despite similar levels of total Cdc5p(Figure 3-figure supplement 4). This result recapitulated previous work showing the cohesin-dependent binding of Cdc5p at CARs(Mishra et al, 2016;Pakchuen et al, 2016). A few small peaks of binding were observed at centromere and RDN regions, but they coincided with false positives in the GFP-control.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Upon Mcd1p-AID depletion, the binding of Cdc5p was abolished genome-wide (Figure 3 and Figure 3-figure supplement 1, Figure 3-figure supplement 2, Figure 3-figure supplement 3), despite similar levels of total Cdc5p(Figure 3-figure supplement 4). This result recapitulated previous work showing the cohesin-dependent binding of Cdc5p at CARs(Mishra et al, 2016;Pakchuen et al, 2016). A few small peaks of binding were observed at centromere and RDN regions, but they coincided with false positives in the GFP-control.…”
supporting
confidence: 89%
“…In this study, we provide important clues on how the regulation of condensin by cohesin and Cdc5p is important for the folding of the RDN. First, cohesin is required for the initial recruitment of Cdc5p to chromosomes in mid-M (this study, and (Mishra et al, 2016;Pakchuen et al, 2016)). We showed that cohesin recruitment of Cdc5p to chromosomes promotes Cdc5p binding to neighboring condensin.…”
Section: Cdc5 Recruitment To the Condensin-bound Region Of The Rdn Stmentioning
confidence: 84%
“…Furthermore, two foreign genes, including those encoding HAUS augmin-like complex subunit 5 (ESA01078.1) and polo kinase (ESA11624.1), are functionally related to mitosis. Polo kinases can regulate mitosis by triggering mitotic exit and facilitating removing centromeric cohesin (Mishra et al, 2016 ; Rodriguez-Rodriguez et al, 2016 ). The HAUS augmin-like complex plays an important role in mitotic spindle formation, chromosome integrity maintenance, and cytokinesis completion (Goshima et al, 2008 ; Lawo et al, 2009 ; Uehara et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…For cell cycle assays, logarithmically grown cultures at 25˚C were treated with alpha factor for G1 arrest (3 μM), hydroxyurea (HU, 0.1 M) for S-phase and nocodazole (20 μg/ml) for G2/M arrest, respectively for 90 to 120 minutes. Cell cycle arrest was confirmed by FACS and microscopic analysis for nuclear morphology as described previously [8,90]. Anti-HA antibody (12CA5, Roche Inc) was used to detect HA-tagged Cse4, rabbit polyclonal antibodies against histone H3 (ab1791, Abcam) to detect histones.…”
Section: Protein Stability Assaysmentioning
confidence: 99%